ANALISA KECEPATAN DINAS TERHADAP DESAIN LAMBUNG KAPAL TANKER 1214 DWT - Achdri Oloan; M. Alfan Ilhamsyah Putra; M Abdul Wahid; Abdul Rohman; Khairul Muzaka (Politeknik Negeri Madura, 2025)
A tanker is a type of ship designed for loading oil and other liquid products. This ship, in its operation, experienced delays in cargo delivery, one of which was due to inadequate ship speed. In planning the service speed, it can affect the shape of the tanker hull. A good ship hull design has a large cargo capacity and a small ship resistance. Therefore, this final project analyzes changes in ship hull design due to variations in ship service speed. There are 3 ship hull models (A, B, C) and service speeds (10,11,12 Knots). Hull A with ship resistance at 10 knots of 39.4 kN and produces an estimated cargo volume of 985,373 m3. Hull B with ship resistance at 11 knots of 48.2 kN, and produces an estimated cargo volume of 973,725 m3, and Hull C with ship resistance at 12 knots of 59.4 kN, and produces an estimated cargo volume of 958,633 m3. Keywords: Tanker, Speed, Hull, Resistance, Volume.